EVALUASI PROGRAM PEMBERDAYAAN PEREMPUAN MELALUI PELATIHAN MENJAHIT DI SANGGAR KEGIATAN BELAJAR (SKB) KOTA SERANG - Dharma Sugana, Muhammad Treynadi Bio; Sudrajat, Indra (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2023)
Evaluation is conducted to determine the effectiveness of the program and provide recommendations for future program improvements. The method used in this research is descriptive method with a qualitative approach. Data was collected through interviews, observation, and documentation. The results showed that the sewing training program at the Serang City SKB had a positive impact on the participants, especially in improving sewing skills and economic empowerment. However, there are several obstacles in the implementation of the program, such as the lack of support from the government and the lack of adequate facilities. Therefore, it is suggested that the sewing training program at SKB Serang City continue to be improved by improving facilities and increasing support from the government. In addition, periodic evaluations need to be carried out to ensure the program is running well and providing optimal benefits for the participants.